Non-interference of Bovine-Human reassortant pentavalent rotavirus vaccine ROTASIIL® with the immunogenicity of infant vaccines in comparison with a licensed rotavirus vaccine. Issue 37 (5th September 2018) - Desai, Sajjad; Rathi, Niraj; Kawade, Anand; Venkatramanan, Padmasani; Kundu, Ritabrata; Lalwani, Sanjay K.; Dubey, A.P.; Venkateswara Rao, J.; Narayanappa, D.; Ghildiyal, Radha; Gogtay, Nithya J; Venugopal, P.; et al.
Abstract: Background: A newly developed bovine-human reassortant pentavalent vaccine (BRV-PV, ROTASIIL®) was tested for its potential effect on the immunogenicity of concomitantly administered EPI vaccines in infants in a randomized controlled study in India. Methods: In this Phase III, multicenter, open label, randomized, controlled study, three doses of BRV-PV or two doses of Rotarix® and one dose of placebo were given to healthy infants at 6, 10, and 14 weeks of age. Subjects also received three doses of DTwP-HepB-Hib (diphtheria, tetanus, whole-cell pertussis, hepatitis B, and haemophilus influenzae type b conjugate – pentavalent vaccine) and oral polio vaccine concomitantly at 6, 10, and 14 weeks of age and a single dose of inactivated polio vaccine at 14 weeks of age. Blood samples were collected four weeks after the final vaccination to assess immune responses to all the vaccines administered. For diphtheria, tetanus, hepatitis B, Hib, polio type 1, and polio type 3 antibodies, non-interference was to be supported if the lower limit of the two-sided 90% confidence interval (CI) for the seroprotection rate difference for the BRV-PV group minus the Rotarix® group was >10.0%. For pertussis antibodies, non-interference was to be supported if the lower limit of the two-sided 90% CI for the ratio of geometric mean concentrations (GMCs) was >0.5. Results: A total of 1500 infants were randomized to either BRV-PV (1125 infants) or Rotarix® (375 infants), of which 1341 completed the study as per the protocol. More than 97% of subjects achieved seroprotective antibody titres against diphtheria, tetanus, hepatitis B, Hib, polio type 1, and polio type 3 in both groups. The difference in seroprotection rates between the BRV-PV group and the Rotarix® group for all these antibodies was less than 1%. The ratio of GMCs of anti-pertussis IgG concentrations for the BRV-PV group versus Rotarix® was 1.04 [90% CI: 0.90; 1.19]. Conclusion: BRV-PV does not interfere with the immunogenicity of concomitantly administered routine infants vaccines.